Keep me warm at Christmas - Novak, Brenda (Novak, Brenda. Silver Springs., 2021)
When a near-fatal accident leaves her with a debilitating facial scar, a once-promising Hollywood starlet retreats to her producer's Silver Springs estate to house sit where she discovers she has a handsome new roommate.